2020
DOI: 10.5897/ijfa2020.0779
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and cultural values of two species of crabs (Cardisoma armatum Herklots and Callinectes amnicola Rochebrune) in Southern Benin, Africa: Management of post-harvest losses and exoskeletons

Abstract: Crabs play an important economic and bio-ecological role in most aquatic ecosystems and occupy an important place in the variety of trophic niches. Callinectes amnicola Rochebrune and Cardisoma armatum Herklots are two edible species widely exploited in Benin. The present work aims to i) evaluate the socioeconomic and cultural importance of those two crab species, ii) analyze the dynamics of the value chain, and iii) monitor the flow of their resources. Surveys were carried out during February 2018 to Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In the Cross River State and Nigeria as a whole, crabs are harvested in the wild as there is currently no crab farming, notwithstanding the many prospects reported for this species and other portunid crabs (Moruf and Lawal-Are, 2017). Mikpon et al (2020) also reported that most economically important aquatic resources, including crabs, are harvested by both industrial and artisanal fisheries in an unsustainable and uncontrollable manner. This excessive focus on the wild crab to support the stocking population can put undue pressure on the crab stock, resulting in overexploitation, reducing genetic diversity, and jeopardising this important resource (Zhang et al, 2021;Sakib et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In the Cross River State and Nigeria as a whole, crabs are harvested in the wild as there is currently no crab farming, notwithstanding the many prospects reported for this species and other portunid crabs (Moruf and Lawal-Are, 2017). Mikpon et al (2020) also reported that most economically important aquatic resources, including crabs, are harvested by both industrial and artisanal fisheries in an unsustainable and uncontrollable manner. This excessive focus on the wild crab to support the stocking population can put undue pressure on the crab stock, resulting in overexploitation, reducing genetic diversity, and jeopardising this important resource (Zhang et al, 2021;Sakib et al, 2022).…”
Section: Introductionmentioning
confidence: 99%